New(spaper) evidence of a reduction in suicide mentions during the 19th century US gold rush - Christoph Kronenberg (Health Economics, 2021)
I analyze the relationship between state-level economic shocks and suicides using gold mined in the United States (US) between 1840 and 1860 as a large unexpected economic shock. Mined gold was an unexpected and large economic shock of up to 3.5% of GDP. This provides as good as random variation to the local economy that I use to estimate the effect of economic changes on suicides. Comprehensive mortality data by state and year does not exist for the US for 1840–1860. Thus, I use web-scraped data from a newspaper archive and use suicide mentions per 100,000 pages to proxy for suicides. Overall, results show that mined gold is linked with an apparent reduction in newspaper suicide mentions in line with previous research.
Keywords: 330; economic shock; gold rush; newspaper; suicide